(untitled) (International Journal of Food and Nutritional Sciences, 2021)
This research looks at adaptations to climate change in coastal India, with an emphasis on the efficacy of measures taken by agricultural and fishing communities. Using data from secondary sources, the study examined adaptation strategies, socioeconomic effects, and geographical vulnerabilities. The research shows significant geographic variation in the perceived impacts of climate change, including warming, drying, a higher frequency of floods, and other changes. Agricultural output is most influenced by measures to save water and is the most successful diversification measure among fishing groups. The report additionally notes significant implementation costs and empirical geographic differences in the efficacy of these techniques. "The results show that there is a need to adapt strategies to local conditions and community needs, as a one size fits all approach is not sufficient," concludes Lara. With respect to the research, it finds that raising awareness, enhancing capacity-building, and providing more inclusive financial access are key for heightening coastal communities resilience. These observations are important to develop policies to assist in the sustainable adoption of the coastline of India and in attaining the adopted goals of the SDGs for poverty alleviation and climate action.